Theoretical Approach to Planning Authority (in Terms of the Municipality’s General Plan) (Ius Novum, 2025)
In normative terms, spatial planning constitutes an authoritative means of shaping space. By exercising its planning authority, a municipality influences how property rights are exercised and, in extreme cases, may lead to their deprivation. The law must set limits on this authority by establishing instruments that guarantee adequate protection of property rights. The municipality’s general plan is one such legal instrument, fulfilling the constitutional condition for the admissibility of interference with real estate ownership, which may be based on a statute. It must not only specify the manner in which restrictions are to be introduced, but also provide a source of values that justify such restrictions. The municipality’s general plan meets these conditions. Thus, it becomes not only an important instrument of planning policy but also a crucial mechanism for protecting the property rights of real estate covered by the planning process.
Keywords: planning authority, municipality, general plan, property protection